Analysis of Scientific Literacy and Need to Develop POE-Based Student Worksheet in Dynamic Material for High School - Salsa Kurnia Magfirah; Selma Riyasni; Asrizal Asrizal; Fauziah Ulmi (Jurnal Penelitian Pembelajaran Fisika, 2026)
This research is motivated by the importance of scientific literacy skills in physics learning, especially in dynamics material that requires students to be able to understand concepts, interpret data, and explain scientific phenomena logically. However, students' scientific literacy skills are classified as not yet optimally developed. This study aims to analyze the level of students' scientific literacy and identify the need for the development of Predict-Observe-Explain (POE)-based Student Worksheets (LKPD), especially in dynamics material. This study uses a descriptive method with quantitative and qualitative approaches. The subjects of the study were 30 students of grade XI Phase F2 of Madrasah Aliyah in Pariaman City. Data were obtained through scientific literacy tests, student needs questionnaires, document analysis, and interviews with physics teachers. The results showed that the average scientific literacy ability of students in the indicator of explaining scientific phenomena was 58.66%, the indicator of evaluating and designing scientific investigations was 46.67%, and the indicator of interpreting data and scientific evidence was 46.66%. These results indicate that students' scientific literacy abilities are still categorized as moderate and need to be improved, especially in the ability to design investigations and interpret scientific data. Therefore, it is necessary to develop LKPD based on the POE model which can facilitate prediction, observation, and scientific explanation activities so that it can support the improvement of students' scientific literacy outcomes in dynamics learning.